PERAN SYEKH MUHAMMAD ARIFFIN DALAM PENGAJARAN ILMU KEISLAMAN DI DESA TELUK MAJLIS - Riski Saputra; Nur Agustiningsih (Istoria: Jurnal Ilmiah Pendidikan Sejarah Universitas Batanghari, 2026)
This study discusses the role of Sheikh Muhammad Arifin Banafi in teaching Islamic knowledge in Teluk Majlis Village (1891–1962). Sheikh Muhammad Arifin Banafi was an Islamic scholar who played an important role in the development of Islamic preaching and education within the community. This research aims to examine the role and contributions of Sheikh Muhammad Arifin Banafi in religious and social aspects of society. The research use historical research method, which consists of the stages of heuristics, source criticism, interpretation, and historiography. The data sources were obtained from both primary and secondary materials, including archives, documents, books, and interviews with individuals related to the research object. The collected data were then analyzed using a descriptive-qualitative approach in order to obtain a comprehensive and systematic understanding. The results of the study indicate that Sheikh Muhammad Arifin Banafi was not only an Islamic preacher but also an educator and a respected community leader.